Degradation Pattern of Textile Effluent by Using Bio and Sono Chemical Reactor. (30th March 2020) - Al-Sakkaf, Basem Mohammed; Nasreen, Sadia; Ejaz, Naeem
Abstract : The research study was conducted to design the ultrasonic-assisted electrochemical reactor and the bioreactor/filter to evaluate the potential applicability of biological trickling filter system and to compare the efficiency of two reactors such as SER and TF for the treatment of textile industry effluents. Also the study to design Sonoelectrolytic process for wastewater treatment of textile industry containing strong color, high temperature, suspended particles and dissolved solid particles has been conducted. Effect to environment and health is caused by oxygen demand (BOD), high chemical oxygen demand (COD). The percentage removal efficiency for wastewater treatment of textile industry by using sonoelectrolytic reactor (SER) was found to be higher than 95% at temperature of 25°C and a pH value of 8.9, while for trickling filter (TF), having adsorbent as a filter medium, efficiency was found to be 95%, and optimum conditions obtained were applied for the treatment of different dye samples. Based on experimental outcomes, it is determined that treatment through SER is done faster than trickling filter because in TF the adsorbent capacity decreases with time and is a time-consuming process, but the chance of deposition on electrodes also increases in SER, so both these processes can yield better results if these problems are eliminated.